Surgically relevant normal and variant renal parenchymal and vascular anatomy in preoperative 16-MDCT evaluation of potential laparoscopic renal donors - Steven S. Raman (2018)
OBJECTIVE. Using 16-MDCT, we describe and quantify the frequency and types of renal anatomic variants and findings relevant for preoperative evaluation and surgical planning for potential laparoscopic renal donors. MATERIALS AND METHODS. On 16-MDCT, 126 consecutive potential donors underwent scanning before contrast administration and after IV power injection of nonionic contrast material during the arterial, nephrographic, and excretory phases. On a 3D workstation, CT images were evaluated retrospectively in consensus by three abdominal imagers. The number and branching pattern of bilateral renal arteries and veins, including anomalies of the inferior vena cava and lumbar-gonadal axis, were categorized along with the frequency of incidental findings of the renal parenchyma and collecting system. RESULTS. Major arterial variants including supernumerary and early branching arteries were present in 16% and 21%, respectively, of left kidneys and 22% and 15%, respectively, of right kidneys. Major and minor venous variants were detected in 11% and 58% of left kidneys and 24% and 3% of right kidneys. Late confluence of the venous trunk was identified in 17% of left kidneys and 10% of right kidneys. Incidental parenchymal and urothelial abnormalities, most commonly cysts and calyceal calcifications, were identified in 30% of the kidneys. Other relevant incidental findings included focal infarcts, cortical scars, atrophic scarred kidney, and bilateral papillary necrosis. Urothelial variants included bilateral simple ureteroceles and right-sided complete duplicated collecting system. CONCLUSION. 16-MDCT angiography and urography allow confident detection and classification of a variety of anatomic and incidental anomalies relevant to the preoperative selection of potential laparoscopic renal donors and to surgical planning. © American Roentgen Ray Society.